Il Tirocinio Diretto Digitale Integrato (TDDI) Il progetto sperimentale per lo sviluppo delle competenze delle maestre e dei maestri - Biagioli, Raffaella; Oliviero, Stefano (Strumenti per la didattica e la ricerca, 2022)
The integrated direct digital apprenticeship represents a new and crucial experimental apprenticeship modality with the primary function of guaranteeing everyone the possibility of living this entire pre- professional experience through virtual modalities and widening and enriching training opportunities for future pre-primary teachers and primary teachers. The experimental project arose from the need to respond to the need to guarantee the practicability of professional training courses at a time when, due to the pandemic, it was not possible to accommodate all students in schools. It was designed with the Regional School Office of Tuscany and resulted from the degree course constant commitment to the USR Tuscany to guarantee students; right to study and enhance the schools; willingness to accommodate trainees.